Colitis in spondyloarthritis - Muhammed Hafis; Vikas Agarwal (Indian Journal of Rheumatology)
Inflammatory bowel disease (IBD) is seen in up to 14% of patients with spondyloarthritis (SpA) with a lower prevalence seen in the Asian population. Conversely, SpA is the most common extraintestinal manifestation in IBD, with prevalence ranging from 10% to 39%. Apart from the strong Class I human leukocyte antigen B27 link for both diseases, several new shared genetic risk loci are identified from genome-wide association studies. Demonstrable mucosal inflammation of gut is present in most of the patients with SpA, even in the absence of clinically overt IBD. Mucosal inflammation leads to disruption of the epithelial barrier and activation of antigen-presenting cells and T-helper cells, which then home to synovium to cause inflammation maintaining the gut synovial axis. Several putative gut bacteria are implicated in the pathogenesis of SpA. IBD must be suspected in all patients of SpA presenting with abdominal pain, diarrhea, unexplained weight loss, anemia, or other malabsorption features. Fecal calprotectin is emerging as a noninvasive screening tool for detecting clinically silent IBD in patient with SpA. Several therapeutic targets have emerged in the last few years based on the understanding of the pathogenic mechanism and have considerably changed the management of both IBD and SpA.